Pengaruh Kinerja Keuangan dan Manajemen Risiko terhadap Return Saham di Bei - Susri Eka Marselina; F. Defung; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
Objective of this study was to examine the effect of financial performance and risk management to return stock at PT. Telekomunikasi Indonesia Tbk. The financial performance is measured by debt to equity ratio (DER), return on equity (ROE), total asset turnover (TATO), and interest rate (IR).Sample of research is PT. Telekomunikasi Indonesia Tbk listed on the Indonesia Stock Exchange (BEI) in the period 2006-2015. Collecting data this study uses secondary data obtained from websate. This study uses SPSS to analyze the data analysis.The results showed that the TATO and IR negative effect, but the DER and ROE does not negatively affect stock return. Overall, the researchers found that some of the most high risk and impact of the likelihood that the risks associated with Indonesia as well as risks related to the business of PT. Telkom. As an alternative actions that can be done by PT. Telkom to address these risks is to reduce risk.Keywords: Debt to equity ratio (DER), return on equity (ROE), total asset turnover (TATO), risk management, stock returns.